Effect Of Treadmill Training On Total Lung Capacity Among Male Kabaddi Players (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of the study was to effect of treadmill training on total lung capacity among male kabaddi players. To achieve the purpose of the present study, twenty four students from A.V.V.M Sri Pushpam College, Thanjavur, Tamilnadu, India were selected as subjects at random and their ages ranged from 18 to 25 years. The subjects were divided into three equal groups of eight each. Experimental group I was exposed to 50% Intensity of treadmill training, experimental group II was exposed to 75% Intensity of treadmill training and control group was exposed to no training. The duration of experimental period was 12 weeks. The pre test and post test scores were subjected to statistical analysis using Analysis of Covariance (ANCOVA) and Scheffe’s post-hoc test. The experimental groups had shown significant differences on total lung capacity after training for a period of twelve weeks.